Development and Characterization of Anti-Nitr9 Antibodies. (24th September 2012) - Shah, Radhika N.; Rodriguez-Nunez, Ivan; Eason, Donna D.; Haire, Robert N.; Bertrand, Julien Y.; Wittamer, Valērie; Traver, David; Nordone, Shila K.; Litman, Gary W.; Yoder, Jeffrey A.
Abstract : The novel immune-type receptors (NITRs), which have been described in numerous bony fish species, are encoded by multigene families of inhibitory and activating receptors and are predicted to be functional orthologs to the mammalian natural killer cell receptors (NKRs). Within the zebrafish NITR family, nitr9 is the only gene predicted to encode an activating receptor. However, alternative RNA splicing generates three distinct nitr9 transcripts, each of which encodes a different isoform. Although nitr9 transcripts have been detected in zebrafish lymphocytes, the specific hematopoietic lineage(s) that expresses Nitr9 remains to be determined. In an effort to better understand the role of NITRs in zebrafish immunity, anti-Nitr9 monoclonal antibodies were generated and evaluated for the ability to recognize the three Nitr9 isoforms. The application of these antibodies to flow cytometry should prove to be useful for identifying the specific lymphocyte lineages that express Nitr9 and may permit the isolation of Nitr9-expressing cells that can be directly assessed for cytotoxic (e.g., NK) function.